Reducing waste in knowledge work at the workplace: a virtual experience : an exploratory study on the impact of virtual working on waste reduction in the Lean Management framework, in organizations - Sanboran, Yanika (My University, 2021)
Due to the Covid-19 pandemic, many organizations that did not do so before have switched to working virtually. At the same time, an increasing number of businesses are adopting the frameworks of Lean Management and Continuous Improvement in attempts to reduce waste in their knowledge work processes. The purpose of this study is to explore the impact of virtual collaboration on waste reduction in organizations. The research assesses how virtual working affects organizations’ collaborative process, and what wastes organizations have before and after the introduction of full-scale virtual working. Through six focus groups, six teams from different organizations, five from Thailand and one from the Netherlands, were interviewed about waste and collaboration within their teams since virtual working. Interview results are discussed in detail, seen in the light of existing literature. To further explore collaboration, surveys that include questions about Teamwork Quality in a virtual setting were distributed to all focus group participants. While it is yet unclear whether virtual collaboration only has positive or negative impacts on waste reduction, the impacts are apparent. Results show that different teams are impacted differently. This could be linked to the way that organizations use technologies to support virtual working, as well as differences in organizational and national cultures. Future research should explore this further, taking into account the framework provided by this study and adding more elements to it.
Keywords: Virtual collaboration, Waste, Lean, Continuous Improvement